Pengembangan Media AI Gemini Berbasis Problem Based Learning pada IPA di SD Inpres 2 Talise - Naisya Faradillah; Najwa Najwa; Nadila Nadila; Iqma Zam-zani; Karin Fitria; Nur Afni; Evatu Nurul Siam; Nur Hani (CV. SINAR HOWUHOWU, 2026)
This study aims to develop a learning media based on Gemini Artificial Intelligence integrated with the Problem Based Learning model for fifth-grade science learning at SD Inpres 2 Talise. The study employed a Research and Development method using the Analysis, Design, Development, Implementation, and Evaluation development model. The research subjects consisted of one fifth-grade teacher, sixteen fifth-grade students, and a media expert validator. Data were collected through validation sheets, teacher response questionnaires, and student interviews. The data were analyzed using a Likert scale and presented in percentage form. The results show that the developed learning media achieves a validity score of 98.1%, which is categorized as highly valid. The practicality test results indicate that the teacher response reaches 100% and the student response reaches 99.75%, both categorized as highly practical. The developed media creates a more engaging, interactive, and enjoyable learning environment and increases student participation in science learning activities. Therefore, the Gemini Artificial Intelligence-based learning media integrated with the Problem Based Learning model is suitable for use as an innovative digital learning medium in elementary school science education.